Penerapan Kompetensi Manajerial Kepala Sekolah dalam Mewujudkan Prestasi non-akademik di Kabupaten Gunungkidul - mulyanto; Etik Nugrahawati (Universitas Sarjanawiyata Tamansiswa, 2022)
This study aims to analyze: (1) managerial competence of school principals in planning school programs at State Elementary School Gunungkidul Regency, (2) supporting and inhibiting factors of the principal's managerial competence in realizing non-academic achievements of schools at State Elementary School Gunungkidul Regency, (3) the results of the application of principal managerial competence in realizing non-academic achievements at Tileng 1 Girisubo State Elementary School and Semanu 3 State Elementary School Semanu, Gunungkidul Regency. This type of research used a qualitative approach. The results of the research data analysis showed that: (1) the application of the principal's managerial competence in planning school program plans had been carried out well, (2) the supporting factors consist of: the principal was an artist, the support of a good school committee, potential teachers and employees and willing to work hard, and there was a clear program plan. While the obstacles in general lie in the lack of budget and inadequate facilities and infrastructure, (3) The results of the application of the principal's managerial competence in realizing school non-academic achievements were very encouraging, because they had won various championships at various levels. Keywords: managerial competence, principal, non-academic achievement